ANALISIS KEMAMPUAN PSIKOMOTORIK MAHASISWA SEMESTER III PROGRAM STUDI PENDIDIKAN KIMIA UNIVERSITAS MUHAMMADIYAH PONTIANAK - Hilda Weny Jayanti; Rody Putra Sartika; Rizmahardian Azhari Kurniawan (Universitas Muhammadiyah Pontianak, 2016)
ABSTRACTLearning assessment includes three aspects of learners abilities which are the cognitive ablilities (knowledge), affective abilities(attitude), and psychomotoric abilities(skills). Cognitive abilities tend to be highlighted than affective and psychomotoric abilities. The psychomotoric abilities of student chemistry education department in Muhammadiyah Pontianak University, should be evaluated since the beginning. Therefore, it is necessary to conduct a research about of psychomotoric abilities of the third semester students of Chemistry Education Muhammadiyah Pontianak University. This study was conducted using descriptive qualitative approach on 16 students using validated observation shet and interview. The results showed that students average psychomotoric abilities was 73.24%. About 1 student has an excellent categories and 15 students with good categories. However, there some aspect of students psychomotoric abilities which were categorized as poor and very poor.Keywords: analysis, psychomotor ability, students of chemical education